(Co-)gasification characteristics and synergistic effect of hydrothermal carbonized solid/liquid products derived from fresh kitchen waste. (December 2022) - Zeng, Mingxun; Ge, Zefeng; Ma, Yuna; Zha, Zhenting; Wu, Yuqing; Zhang, Huiyan
Highlights: A scheme of HTC coupled with co-gasification was proposed and confirmed. Fresh kitchen waste with original moisture was used for HTC process. Synergistic promotion effect mainly occurred in coke co-gasification stage. Process water contained 785.82 mg/L of K, catalyzing the coke co-gasification. Abstract: Kitchen waste has high moisture and rich organics, which can be transformed into hydrochar by hydrothermal carbonization (HTC) and then used for gasification efficiently. But process water (liquid product from HTC, containing organic compounds) has not been well utilized in the way of thermochemistry. In this study, a scheme of co-gasification of solid and liquid products of kitchen waste HTC process was proposed, and the separate gasification and co-gasification were studied. The results showed that after HTC process, the obtained hydrochar size became smaller and uniform, and the high heating value increased from 19.90 MJ/kg to 28.03 MJ/kg. The carbon skeleton of hydrochar was mainly composed of aromatic and alkyl C, which was easily converted into coke during gasification. Process water mainly contained pyrazine organics, and its C and N content were 18.94 g/L and 3.25 g/L, respectively. The co-gasification syngas yield of solid and liquid products was significantly higher than the calculated total yield of separate gasification. There was obvious synergistic effect in the coke co-gasification stage, and the H2 production was 1.24 times of the calculated value. Synergistic effect was mainly caused by the introduction of process water, which contained 785.82 mg/L of K and would catalyze the coke co-gasification. HTC coupled with co-gasification is an efficient disposal for kitchen waste with high moisture.